Reconciling faceted search and query languages for the Semantic Web. (14th August 2012) - Ferré, S.; Hermann, A.
Faceted search and querying are two well-known paradigms to search the Semantic Web. Querying languages, such as SPARQL, offer expressive means for searching RDF data sets, but they are difficult to use. Query assistants help users to write well-formed queries, but they do not prevent empty results. Faceted search supports exploratory search, i.e., guided navigation that returns rich feedbacks to users and prevents them to fall in deadends (empty results). However, faceted search systems do not offer the same expressiveness as query languages. We introduce Query-based Faceted Search (QFS), the combination of an expressive query language and faceted search, to reconcile the two paradigms. We formalise the navigation of faceted search as a navigation graph, where navigation places are queries and navigation links are query transformations. We prove that this navigation graph is safe (no dead-end) and complete (every query that is not a dead-end can be reached by navigation). In this paper, the LISQL query language generalises the existing semantic faceted search systems and covers most features of SPARQL. A prototype, Sewelis, has been implemented and a usability evaluation demonstrated that QFS retains the ease-of-use of faceted search and enables users to build complex queries with little training.